ROLE AND FUNCTION OF GENERAL GOVERNMENT PROPERTIES AS A GUIDE OF STATE ADMINISTRATION OFFICERS IN RUNNING ITS BUSINESS - Mukmin Muhammad (Meraja journal, 2019)
[Full Paper] to pdf Copyright (c) 2018 Meraja journal